Participation of Iranian Cerebral Palsy Children in Life Areas: A Systematic Review Article - PASHMDARFARD, Marzieh; AMINI, Malek; HASSANI MEHRABAN, Afsoon (Iranian Journal of Child Neurology, 2017)
How to Cite This Article: Pashmdarfard M, Amini M, Hassani Mehraban A. Participation of Iranian Cerebral Palsy Children in Life Areas: A Systematic Review. Iran J Child Neurol. Winter 2017; 11(1):1-12. Abstract Objective Cerebral palsy (CP) is the most common cause of chronic disability that restricts participation in areas of occupations for children. The main aim of rehabilitation is enhancement of their clients for participation in occupations. The aim of this study was to overview of the factors influencing the participations of children with CP in Iran. Materials & Methods A systematic, evidence-based process (Duffy 2005) was used. For data gathering electronic databases including Google scholar and Iranian and foreigner famous journals in the fields of pediatrics, were used. The main key words for search were Activity of Daily Living (ADL), Instrumental Activity of Daily Living (IADL), play, leisure, work, rest/sleep, social participation, and education. All the papers of this study were about the factors influencing the participation of Iranian CP children during 2000-2016. Totally, 156 articles were found eligible as for Iranian CP children study, of which 100 articles were discarded. Because of repetitive and duplicability of some articles, 17 articles were removed as well. Results The most studies about Iranian CP children participations in life areas were in the ADL area of participation (N=12), and the lowest articles were in the area in the field of: Work (N=2), play (N=2), and sleep/rest (N=2). Most of the occupational therapists do not focus on the all life areas. Conclusion In Iran, many researchers do not pay attention to the participation of CP children. Many articles just paid attention to the sensory, motor or cognitive components of their clients. Refereneces 1.Trabacca A, Vespino T, Di Liddo A, Russo L. Multidisciplinary rehabilitation for patients with cerebral palsy: improving long-term care. J Multidiscip Health c 2016;22(9):455-462. 2. shubhra M, Deborah J. cerebral palsy. In: Braddom RL, editors. physical Medicine & Rehabilitation. 3rd ed. Elsevier; 2007. p.1243-61. 3. Van Nieuwenhuizen O, Platenga NJ, Kasteel TE. Epilepsy in cerebral palsy: etiology, classification and prevalence. Europe Paed Neural Soc 1997;1(2-3):111-5. 4. Oriady Zanjani M. Cerebral palsy in viewpoint of speech language pathology nature, assessment and treatment. Hamedan: Nooreelm; 2005. 5. Joghataei M, Kazem M. Assessment the level of community needs in welfare services on the whole country. 1st ed. Tehran: University of Social Welfare and Rehabilitation Sciences; 1990.p.123-5. 6. Vohr BR, Wright LL, Dusick AM. Differences and outcomes of extremely low birth weight infants. Pediatrics 2004;113(4):781-9. 7. sharifi A, Kamali M, Chabok A. Rehabilitation Needs of People with Cerebral Palsy: a qualitativeStudy. Med J Islam Repub Iran 2014;28:1-10. 8. labaf S, Shamsoddini A, Hollisaz MT, Sobhani V, Shakibaee A. Effects of Neurodevelopmental Therapy on Gross Motor Function in Children with Cerebral Palsy. Iran J Child Neurol 2015;9(1):36-41. 9. Shamsoddini A. comparison between the effect of neurodevelopmental treatment and sensory integration therapy on gross motor function in children with Cerebral Palsy. Iran J Child Neurology 2010;14(1):31-8. 10. American Occupational Therapy Association. Occupational Therapy Practice Framework: Domain and Process, 3rd Edition. Am J Occup Therapy 2014;48:3-48. 11. Bradley L, Law M. systematically reviewing the evidence. In: Law M, editors. Evidence-based rehabilitation: A guide to practice. 2nd ed. USA: Slack Incorporated; 2008. p.143-7. 12. Dalvand H, Dehghan L, Feizy A, Amirsalai S, Bagheri H. Effects of the bobath technique, conductive education and education to parents in activities of daily living in children with cerebral palsy. Hong Kong J Occup Therapy 2009;19(1):14–9. 13. Nurani Gharaborghe S, Sarhady M, Hosseini SMS, Mortazavi SS. Relationship between Quality of Life and Gross Motor Function in Children with Cerebral Palsy (Ages 4-12) Medical Journal of Tabriz University of Medical Sciences and Health Services 2015;37(2):48-53. 14. Afshar S, Rassafiani M, Hosseini S.A. Effect of Occupational Therapy Home Program on Activities of Daily Living of 5-12 Years Old Children. J Rehabil 2013 13(4):117-23. 15. Lewandowska A, Zajchowska J, Iwaniszyn J, Huk J, Świeboda P, Filip R. Functioning of the family of a child suffering from cerebral palsy. J Pre-Clin Clin Res. 2012; 6(1): 50-53. 16. Razavi Afzal Z-S, Rassafiani M, Sarfaraz Z, Malekpour M, Salehi, M. A Survey on caregivers’ knowledge about special caring for 1-to-5 year-old children with cerebral palsy and their compliance with these practices. J Res Rehabil Sci 2013;9(4):618-28. 17. Rassafiani M, Sahaf R. Hypertonicity in Children with Cerebral Palsy: a New Perspective. Iran Rehabil J 2011;9:66-74. 18. Poursadoughi A, Dadkhah A, Pourmohamadreza-Tajrishi M, Biglarian A. Psycho-Rehabilitation Method (Dohsahou) and Quality of Life in Children with Cerebral Palsy. Iran Rehabil J 2015;13(2):28-33. 19. Salehi Dehno N, Noorizadeh Dehkordi S, Dadgoo M, Salehi M. Association between spasticity and the level of motor function with quality of life in community dwelling Iranian young adults with spastic cerebral palsy. Med J Islam Repub Iran 2012;26(4):150-6. 20. Noori M, Pishyareh E, Hosseini SA, Akbarfahimi N, Rahgozar M. Relationship between upper extremity function and quality of life in the children with spastic cerebral palsy in Capital of Iran. Pajouhan Scientific Journal 2015;13(3):41-8. 21. Dalvand H, Rassafiani M, Hosseini S.A. Handling challenges in the children with cerebral palsy: A qualitative content analysis. J Res Rehabil Sci 2013;9(8):1267-80. 22. Balouchy R, Ghaeni S. Physical Fitness of The Children Infected With Cerebral Paralysis Through A work-group of “Therapists - Children - Parents”. Scientific Journal of Ilam University of Medical Sciences 2009;17(3):16-23. 23. Dalvand H, Rassafiani M, Hosseini S.A. Handling in the Children with Cerebral Palsy: A Review of Ideas and Practices (A Literature Review). J Rehabil 2012;13(5):8- 17. 24. Hassani M, Hassani Mehraban A, Taghizadeh G, Aliabadi F, Ramezani S. Enjoyment of participation in formal and informal activities among students with cerebral palsy and healthy students. J Kermanshah Univ Med Sci 2015;19(3):160-7. 25. Nobakht Z, Rassafiani M, Rezasoltani P. Influence of child’s disability on encountering environmental barriers to Participation of children with cerebral palsy. J Res Rehabil Sci 2013;9(2):286-94. 26. Ghasemzadeh R, Kamali M, Chabok A, Falahi M, Shirani M. Accessibility to the public facilities: a mean to achieve civil rights of the people with disabilities in Iran. Iran Rehabil J 2008;6(7,8):73-82. 27. PourRanjbar M, Keshavarz L, Sharifian E, Farahani A. Barriers for Wheelchair-User Disabled People to Participate in Leisure Physical Activities in Southeast of Iran. Journal of Kerman University of Medical Sciences 2015;22(5):555-68. 28. Hassani Mehraban A, Hassani M, Amini M. The Comparison of Participation in School-Aged Cerebral Palsy Children and normal Peers: A Preliminary Study. Iran J Pediatr 2016 June; 26(3):e5303. doi: 10.5812/ijp.5303 29. Nobakht Z, Rassafiani M, Rezasoltani P, Sahaf R, Yazdani F. Environmental barriers to social participation of children with cerebral palsy in Tehran. Iran Rehabil J 2013;11:40-5. 30. Abbaskhanian A , Rashedi V , Delpak A, Vameghi R, Gharib M. Rehabilitation Interventions for Children with Cerebral Palsy: A Systematic Review. J Pediatr Rev 2015;3(1):1-8. 31. Amini M, Hassani Mehraban A, Haghni H, Asgharnezhad AA, Khayatzadeh Mahani M. Development and validation of Iranian children’s participation assessment scale. Med J Islam Repub Iran 2016 (20 February). Vol. 30:333. 32. Rosenberg L, Jarus T, Bart O. Development and initial validation of the children participation questionnaire(CPQ). Disability Rehabil 2010;32(20):1633-44. 33. Amini M, Hassani Mehraban A, Rostamzade O. Translation, cultural adaptation, face, content and convergent validity of children participation questionnaire into Persian. J Rehabil Med 2016; 5(2): 151-157. 34. Soleimani F, Vameghi R, Kazemnejad A, Akbar Fahimi N, Nobakht Z, Rassafiani M. Psychometric Properties of the Persian Version of Cerebral Palsy Quality of Life Questionnaire for Children. Iran J Child Neurol 2015;9(1):76-86.